Annular pancreas in adults: a tertiary care institute experience and review of literature - Senthil Kumar, Perumal; Sugi, R. V. Subramaniam; Jeswanth, Sathyanesan; Ravichandran, Palaniappan (International Surgery Journal, 2018)
Annular pancreas (AP) in adults is a rare congenital anomaly characterized by the presence of ectopic pancreatic tissue surrounding the second part of the duodenum. This rare embryologic abnormality is usually detected after development of complications or as incidental finding in most cases. Diagnosis and treatment strategies for symptomatic adult AP remain controversial. No clearly defined specific guidelines and treatment protocols exist about management of adult AP, therefore, treatment and operative approaches must be individualized for each patient. It is always prudent to consider the possible post-operative complications, surgical treatment should be reserved only for cases where there is complete obstruction.